Slip behavior during pressure driven flow of Laponite suspension - Kamdi, Prophesar M.; Orpe, Ashish V.; Kumaraswamy, Guruswamy (Physics of Fluids, 2021)
We investigate pressure driven pipe flow of Laponite suspension, as a model thixotropic fluid. The tendency of the suspension to age is controlled by addition of sodium chloride salt to vary the ionic strength. We use a syringe pump to prescribe the flow and observe that a steady state flow is obtained. Unusually, the steady state pressure drop required to maintain a constant flow rate decreases with an increase in the flow rate, in qualitative contrast to the expectation for Poiseuille flow. We demonstrate that experimental results obtained by varying the flow rate, salt concentration, and flow geometry (pipe diameter and length) can be collapsed onto a single universal curve that can be rationalized by invoking slip of the suspension at the tube walls. The Laponite suspension exhibits plug-like flow, yielding at the tube walls. Our results suggest that the slip length varies linearly with the flow rate and inversely with the tube diameter.